Rebag-Ware: Reputation-based Governance of Public Works - Roberto Confalonieri; Cristiano Leoni; Lucio Picci (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2007)
Reputation-based Governance (Rebag) is a framework to address governance problems that hinges on the reputation of the relevant actors. It functions thanks to an appropriate Web-based information system that encompasses the concept of Internet-based Reputation System, of which eBay represents an example. Rebag-Ware is a demonstrator of such an information system, showing an application of the proposed governance model to the management of public works. Rebag provides strong incentives to the actors of governance to behave efficiently and honestly. It allows for the computation of routine statistics that are used to fight corruption. Also, it allows for very advanced forms of public involvement that include participative planning and budgeting. In the paper, Rebag-Ware 1.0 is used to show some of the characteristics of the proposed model of governance. The site of the project is http://www.rebag.it. Rebag-Ware can be accessed at: http://fire.ei.unibo.it:8080/rebagware/.
Keywords: 330